2019
DOI: 10.1080/21691401.2019.1593857
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Ras-ERK1/2 signalling promotes the development of osteosarcoma through regulation of H4K12ac through HAT1

Abstract: Histone H4 acetylation at lysine 12 (H4K12ac) has been reported to be associated with the poor prognosis of pancreatic cancer. The study intends to study whether H4K12ac participates in regulating the carcinogenic effect of Ras-ERK1/2 on osteosarcoma (OS). The plasmids of pEGFP-N1, pEGFP-Ras WT and pEGFP-K-Ras G12V/T35S were transfected into MG-63 cells, the protein levels of H4K12ac and ERK1/2 were analyzed by Western blot. Effects of H4K12ac on cell proliferation and migration of MG-63 cells were tested by 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The results of KEGG analysis showed that the DEmRNAs are widely involved in the "PI3K-AKT," "MAPK," and "Ras" pathways. These pathways have been confirmed as regulating the progress of OSA, [29][30][31][32] which indicates that the model we built has research value. In addition, we constructed a PPI network and identified 10 hub genes.…”
mentioning
confidence: 61%
“…The results of KEGG analysis showed that the DEmRNAs are widely involved in the "PI3K-AKT," "MAPK," and "Ras" pathways. These pathways have been confirmed as regulating the progress of OSA, [29][30][31][32] which indicates that the model we built has research value. In addition, we constructed a PPI network and identified 10 hub genes.…”
mentioning
confidence: 61%
“…HAT1 has also been shown to induce apoptosis by upregulating Fas expression in lung cancer cells 46 . In addition, Ras-ERK1/2 signaling has been shown to promote the development of osteosarcoma through the regulation of H4K12Acetyl, via HAT1 47 . We showed that the loss of HAT1 expression was associated with the development of resistance to BRAFi, such as vemurafenib and dabrafenib.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, lncRNA PCAT6, which was reported to regulate miRNA levels, affected the expression of MDM2 possibly through miRNAs, ( 56 – 58 ). Additionally, in MG63 cells, MDM2 was regulated by proteins including Ras-ERK1/2 signaling or GRIM-19 ( 59 , 60 ). Thus, MDM2 could be regulated by lncRNA PCAT6 possibly attributing to the regulation of lncRNA PCAT6 on the upstream proteins of MDM2.…”
Section: Discussionmentioning
confidence: 99%